An investigation on machining characteristics in abrasive water jet machining of hybrid laminated composites with SiC nano particles. (2021) - Selvam, R.; Arunkumar, N.; Karunamoorthy, L.
Abstract: Abrasive Water Jet Machining process is widely employed in the machining of composite materials. In this work, a novel combination of hybrid laminated composite materials is developed, with Carbon and S-Glass fibers as primary reinforcement and filler material as SiC nano particles. An experimental investigation were conducted to assess the influence of abrasive water jet machining process parameters on kerf taper (Kt) and average surface roughness (Ra) of laminated hybrid composites. The effects of process parameters on experimentally obtained quality characteristics (Ra and Kt) values were empirically correlated by generating response surface graphs and also optimized within the tested range based on desirability approach. The optimal combination process parameters are traverse speed of 145 mm/min, abrasive mass flow rate of 115 g/min, water pressure of 200 MPa and stand-off distance of 1 mm. The optimum parameter levels were also confirmed by verification test. It is clear that, for obtaining a better quality characteristics abrasive mass flow rate and water pressure are significant parameters. The machined surfaces were examined with a Scanning Electron Microscope (SEM) to observe the quality of machined composite surface with the optimal settings obtained through response surface method.